Pentingnya Kader Posyandu dalam Pencegahan Stunting dan Stimulasi Perkembangan Anak - Aulia Elvira; Solfema Solfema; Lili Dasa Putri (BADAN PENERBIT STIEPARI PRESS, 2025)
Stunting is a chronic nutritional problem that has a serious impact on children's growth and development. Posyandu cadres have a crucial role in efforts to prevent stunting. This research aims to analyze the role of posyandu cadres in providing nutrition education, monitoring children's growth, and providing stimulation for children's development. The research method used is qualitative with a case study approach. The research results show that posyandu cadres have a very important role in providing nutritional education to pregnant and breastfeeding mothers, monitoring children's growth regularly, and providing stimulation of children's development through posyandu activities. However, there are still several obstacles faced by posyandu cadres in carrying out their duties, such as lacck of knowleedge and skill, as well’s a limited resources.